ADMA, subclinical changes and atrial fibrillation in the general population. (15th January 2016) - Ramuschkat, Meike; Appelbaum, Sebastian; Atzler, Dorothee; Zeller, Tanja; Bauer, Christoph; Ojeda, Francisco M.; Sinning, Christoph R.; Hoffmann, Boris; Lackner, Karl J.; Böger, Rainer H.; Wild, Philipp S.; Münzel, Thomas; et al.
Abstract: Background: Pathways of oxidative stress, nitric oxide bioavailability andl -arginine derivatives are hypothesized to be related to atrial fibrillation (AF). Circulating methylatedl -arginine metabolites can be assessed in the general population and may show an association with AF. Methods: We determinedl -arginine and its metabolites asymmetric dimethylarginine (ADMA), l -N ω -monomethylarginine (NMMA) and symmetric dimethylarginine (SDMA) in the population-based Gutenberg Health Study (n = 5000), mean age 55 ± 11 years, 51% men, in association with clinical variables of AF such as electrocardiographic and echocardiographic measures and manifest AF. Results: Individuals with AF (N = 161), 71% men, were older, mean age 64.9 ± 8.3 years. In Bonferroni-corrected multivariable-adjusted regression analyses we observed moderate inverse associations forl -arginine, SDMA, andl -arginine/ADMA ratio with ventricular heart rate, and forl -arginine andl -arginine/ADMA ratio with QTc interval.l -arginine was correlated with QRS duration. In echocardiographic analyses, SDMA was related to left atrial diameter and deceleration time, ADMA and NMMA were correlated with left ventricular mass. ADMA (odds ratio [OR] 1.21, 95% confidence interval [CI] 1.11-1-32; p = 0.013) and NMMA (OR 1.17, 95% CI 1.09–1.26, p = 0.014) were related to prevalent AF.l -arginine/ADMA ratio was inversely associated (OR 0.8, 95% CI 0.71–0.90, p = 0.0082). Results were similar after adjustment for creatinine. Conclusions: In our large, population-based cohort, we observed moderate associations ofl -arginine metabolites and intermediate electrocardiographic and echocardiographic variables and AF. Our findings support further investigations to define the role ofl -arginine derivatives in AF and their clinical utility.